Are the discoveries directed to applications? Translating the status of translational research in Peshawar, Pakistan - Sarwat Jahan; Salman Zahir; Khansa Khan; Abdul Moez; Emad Khan; Amir Zaman Khan (International Journal of Pathology, 2024)
Background: Translational research plays a pivotal role in transforming basic scientific discoveries into practical applications, such as drugs and treatments, to address community health needs. This study aims to assess the awareness and perceptions of translational research among healthcare professionals in Peshawar, Pakistan. Methods: A cross-sectional descriptive design was employed, with data collected between January and July 2023 from public and private tertiary care hospitals in Peshawar, Pakistan. The study was approved by Ethical review board of Northwest School of Medicine via letter number: IRB & EC/2022-SM/074 dated: 15 Nov 2022. A sample size of 472 healthcare professionals was determined using the OpenEpi sample size calculator. The study utilized a self-structured questionnaire covering demographic information, awareness of translational research, and knowledge of its various aspects. Data analysis was performed using SPSS version 26, employing descriptive statistics and a one-sample t-test. Results: The study included 472 participants, with a mean age of 30.8 years, comprising various healthcare roles. Gender distribution showed 62.7% males and 37.3% females. Only 25% of respondents reported familiarity with translational research, while 75% indicated a lack of awareness. Information sources varied, with conferences/seminars (16.1%) and colleagues (5.5%) being prominent. Regarding the understanding of translational research, 64.2% admitted to having no idea. Identified barriers included lack of resources (14.8%), lack of awareness (7.6%), and lack of a sense of responsibility (1.3%). A significant majority (87.3%) reported poor knowledge of translational research, while only 12.7% indicated good knowledge. Conclusion: The findings highlight a substantial lack of awareness and understanding of translational research among healthcare professionals in Pakistan.